Association of Increased Serum ACE Activity with Logical Memory Ability in Type 2 Diabetic Patients with Mild Cognitive Impairment - Tian, Sai; Han, Jing; Huang, Rong; Xia, Wenqing; Sun, Jie; Cai, Rongrong; Dong, Xue; Shen, Yanjue; Wang, Shaohua (Frontiers in Behavioral Neuroscience, 2016)
Background: Angiotensin-converting enzyme (ACE) is involved in the chronic complications of type 2 diabetes mellitus (T2DM) and Alzheimer’s disease. This study aimed to assess the pathogenetic roles of ACE and the genetic predisposition of its insertion/deletion (I/D) polymorphism in mild cognitive impairment (MCI) among T2DM patients. Methods: A total of 210 T2DM patients were enrolled. Among these patients, 116 satisfied the MCI diagnostic criteria and 94 exhibited healthy cognition. The cognitive functions of the patients were extensively assessed. The serum level and activity of ACE were measured via enzyme-linked immunosorbent assay and ultraviolet spectrophotography. The single-nucleotide polymorphisms of the I/D gene of ACE were analyzed. Results: The serum level and activity of ACE in diabetic MCI patients (p = 0.022 and p = 0.008, respectively) were both significantly higher than those in the healthy controls. A significant negative correlation was found between their ACE activity and logical memory test score (LMT) (p = 0.002). Multiple stepwise regression iterated the negative correlation between ACE activity and LMT score (p = 0.035). Although no significant difference was found in the genotype or allele distribution of ACE I/D polymorphism between the groups, the serum levels and activity of ACE were higher in the DD group than in the ID and II groups ( p < 0.05). Conclusions: Serum ACE activity could better predict logical memory in T2DM patients than ACE level. Further investigations on a large population size are necessary to test whether the D-allele of the ACE gene polymorphism is susceptible to memory deterioration.